DESIGN AND SIMULATION OF AUTOMATIC TEMPERATURE CONTROL AND ALERT SYSTEM BASED PIC16F887 - Jahlool, Jabbar Shaati (APTIKOM Publisher, 2017)
In this research, the design and simulation of an automatic system for temperature control using embeddedsystem in order to automatically control of multi appliances depend on the temperature value. The appliances will becontrolled are ventilation, cooling, heating and alert. This is an order to avoid or reduce to human intervention andincrease system reliability. An important feature of this automation process is to reduce or eliminate the possibility ofrelying on the human factor operator for industries, warehouses and laboratories, and to improve working andperformance environments. The system in this paper used the microcontroller PIC16F887 as the central control unit,LM35 temperature sensor as a temperature source,16x2 liquid crystal display (LCD) as indicator to display thedifferent system working status an addition to some of drivers, relay and light emitting diodes (LED) as indicators todisplay the corresponding working appliance driver. The implementation and simulation of the system work has beenachieved by using Proteus professional software v8.0 and mikroc pro for pic v.6.6.1 software to write the equivalentprogram and generate. Hex file for system working.